Interactive effects of seed priming and genetic diversity on rice germination and early growth under drought stress - Ju-Young Choi; Young-Hwan Ju; Seong-Woo Cho; Jae-Buhm Chun; Sun-Hee Woo; Jun-Ichi Sakagami (All Life)
Drought stress during seed germination and early seedling growth limits water uptake, resulting in poor crop establishment. Hydropriming is a cost-effective method to enhance drought tolerance, but its effectiveness across genetically diverse rice varieties remains unclear. This study evaluated hydropriming effects on germination and early growth under drought using 59 genetically diverse rice varieties from the World Core Collection. Seeds were sown in well-watered and drought-stressed soils, and traits measured 14 days after sowing. Hydropriming significantly improved seedling performance in all tested varieties. Compared to non-primed seeds, primed seeds showed 27.2% increase in shoot length, 37.3% in root length, 32.2% in shoot dry weight, and 36.7% in root dry weight. Under drought, strong correlation between leaf area and total root length (r = 0.42, p < 0.05) was observed only in primed seeds, suggesting enhanced root development supports shoot growth. In cluster group 1 of eight drought-tolerant varieties, on day14 after sowing, the proportion of dry weight allocated to roots in primed seeds increased, indicating improved water uptake. In conclusion, seed hydropriming promotes early growth and drought avoidance by enhancing root development and water uptake. Its effectiveness depends on genetic background, supporting genotype specific strategies to improve rice under drought.